Beyond the Rhetoric of Participation: Youth and New Forms of Political Acting - Biffi, Elisabetta (Encyclopaideia, 2023)
The importance of youth participation is underlined by international policies, which widely stress youth’s fundamental role in developing more just and sustainable societies. At the same time, disaffection from the more traditional democratic processes is registered by young people, who instead seem to be looking for forms of expression of a different nature. This paper aims to question the forms of participation of young people, offering to consider them as resources for the broader society within the perspective of public pedagogy (Biesta, 2012), suggesting that the institutions let themselves be informed by what is happening.